Complete sequence and characterization of mitochondrial and chloroplast genome of Chlorella variabilis NC64A. (2nd September 2016) - Orsini, Massimiliano; Costelli, Cristina; Malavasi, Veronica; Cusano, Roberto; Concas, Alessandro; Angius, Andrea; Cao, Giacomo
Abstract: The complete nucleotide sequences of the mitochondrial (mtDNA) and chloroplast (cpDNA) genomes of Chlorella variabilis NC64A (Trebouxiophyceae) have been determined in this study (GenBank accession no. KP271968 and KP271969, respectively). The mt genome assembles as a circle of 78, 500 bp and contains 62 genes, including 32 protein-coding, 27 tRNA and 3 rRNA genes. The overall GC content is 28.2%, while the coding sequence is 34%. The cp genome forms a circle of 124, 793 bp, containing 114 genes, including 79 protein-coding, 32 tRNA and 3 rRNA genes. The overall GC content is 33, 9%, while the coding sequence is 50%.